HUBUNGAN ANTARA TINGKAT KONSUMSI ENERGI DAN ZAT GIZI (PROTEIN DAN VITAMIN C) TERHADAP STATUS ANEMIA MAHASISWI AKADEMI GIZI KARYA HUSADA KEDIRI - admin ilkes (STIKES Karya Husada Kediri, 2017)
Anemia is a condition in which the levels of hemoglobin (Hb) in the blood are less than normal, which is different for each age group and sex. Anemia caused by iron deficiency is called iron nutritional anemia, because iron is one of the nutritional elements that are the components of Hb or red blood cells. Community groups that are prone to anemia are infants, toddlers, adolescents, women of childbearing age, pregnant women, and lactating mothers. In Indonesia the prevalence of anemia in this age group is relatively large, ranging from 40-57%. This study aims to analyze the relationship between the level of energy consumption and nutrients (protein and Vitamin C) on the status of anemia Student Nutrition Academy Karya Husada Kediri The type of research conducted is cross sectional because researchers conduct measurements and observations directly (observasional) at the same time and seen the relationship between cause and effect. The sample is a student of Nutrition Academy Karya Husada Kediri as much as 42 female students. Data on the relationship of energy consumption level and nutrient (protein and Vitamin C) and anemia status were analyzed using Chi square. The result of this research is energy consumption level and nutrient (protein and Fe) of female students obtained the result as follows: Energy consumption level with normal category 64,3% and category less 357%. Protein consumption level with normal category 64,3% and category less 35,7%. Levels of consumption of Vitamin C with normal category of 38.1% and less 61.9% category. Status of anemia female students normal category 23 people (54,8%) and category of anemia 19 person (45,2%). Based on the results of statistical tests obtained the result that there is a relationship of consumption level of Energy, Protein and Vitamin C to the status of anemia with pearson Chi-Square <α (0.001 <0.05) Based on the results of the above study suggested to students are expected to continue to consume foods containing high Vitamin C.